Методика створення електронної аудіокомпозиції - Хіміч, Є. О.; Березова, А. С. (ХНУРЕ, 2025)
The paper is devoted to the analysis of techniques and technologies used in the creation of audio compositions. In the modern media industry, sound plays a crucial role in various formats, including film, advertising, electronic music, and podcasts. The process of creating an audio composition requires both creative and technical skills, involving the use of digital audio workstations (DAW), sound processing, and mixing. Understanding the fundamental aspects of sound design and production allows for achieving a professional audio experience and enhancing the emotional impact of media content.
Keywords: електронна аудіокомпозиція; audio composition